2022
DOI: 10.3390/microorganisms10050863
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Toxoplasma gondii Mitoribosomal Large Subunit Components

Abstract: Mitochondrial ribosomes are fundamental to mitochondrial function, and thus survival, of nearly all eukaryotes. Despite their common ancestry, mitoribosomes have evolved divergent features in different eukaryotic lineages. In apicomplexans, the mitochondrial rRNA is extremely fragmented raising questions about its evolution, protein composition and structure. Apicomplexan mitochondrial translation and the mitoribosomes are essential in all parasites and life stages studied, highlighting mitoribosomes as a prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…However, a comprehensive catalog of mitoribosomal constituents is missing, and the extent to which rRNA fragments are part of mitoribosomes remains unanswered. We selected three short RNAs to test for their presence in high-molecular weight complexes by sucrose gradient analysis of enriched mitochondria (Lacombe et al 2019; Shikha et al 2022). We picked sRNAs that were well detected in RNA gel blot experiments (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a comprehensive catalog of mitoribosomal constituents is missing, and the extent to which rRNA fragments are part of mitoribosomes remains unanswered. We selected three short RNAs to test for their presence in high-molecular weight complexes by sucrose gradient analysis of enriched mitochondria (Lacombe et al 2019; Shikha et al 2022). We picked sRNAs that were well detected in RNA gel blot experiments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Tg mS35 and Tg uL24m coprecipitated with mitochondria-encoded rRNA. Knockdown of Tg mS35, Tg bL35m, Tg bL36m and Tg bL28m resulted in specific loss of activity of one respiratory complex, which is partially encoded in the mitochondrial genome (Lacombe et al, 2019; Shikha et al, 2022). Nevertheless, it remains to be determined whether these large complexes are actively involved in translation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, compelling evidence has surfaced suggesting the existence of ribosome-sized particles, including ribosomal proteins. Using blue-native gel electrophoresis, it was demonstrated that tagged ribosomal proteins Tg mS35, Tg bL12m, Tg uL3m, and Tg uL24m migrate as constituents of a macromolecular complex within the size range of a ribosome ( Lacombe et al, 2019 ; Shikha et al, 2022 ). Additionally, Tg mS35 and Tg uL24m coprecipitated with mitochondria-encoded rRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Two mitochondrially localized RNA binding proteins from the RAP (RNA-binding domain abundant in apicomplexans) family are also essential for the survival of P. falciparum , although their role in RNA metabolism has not yet been determined ( Hollin et al, 2022 ). In addition, the depletion of nuclear-encoded mitoribosomal proteins of T. gondii ( Lacombe et al, 2019 ; Shikha et al, 2022 ) and P. falciparum ( Ke et al, 2018 ) led to defects in the assembly of ETC complexes and in parasite proliferation, suggesting that mitochondrial translation is important for parasite survival. Resistance to the antimalarial drug atovaquone in P. falciparum and T. gondii has been linked to mutations in the cob ( cytB ) gene of mitochondria ( McFadden et al, 2000 ; Srivastava et al, 1999 ; Syafruddin et al, 1999 ), further supporting the idea of active, essential translation in apicomplexan mitochondria.…”
Section: Introductionmentioning
confidence: 99%